A Comparative Evaluation of Salivary Changes and Oral Indices in Pediatric Patients Having Chronic Kidney Disease and Juvenile Diabetes with Healthy Controls - Chaudhary, Shweta; Shimpi, Manasi Rajendra; Shimpi, Rajendra Kashinath; Lakade, Laxmi; Jajoo, Shweta; Desai, Sneha (Journal of Pediatric Nephrology, 2019)
Background and Aim: Chronic Kidney disease is a common condition seen in Juvenile diabetes with 90% of renal impairment patients displaying a wide spectrum of oral manifestations in the hard and soft tissues including changes of the salivary composition and flow rate. There is an increase in the serum cystatin-C, urea and creatinine levels in these patients, which is reflected in the saliva. This study was conducted to assess the changes in salivary levels of cystatin-C, urea, and creatinine as well as oral – Decayed, Missing and Filled Teeth Index (DMFT) and gingival indices in pediatric patients suffering from chronic renal disease and juvenile diabetes and compare them with healthy individuals. Methods: Fifteen patients with juvenile diabetes suffering from chronic renal disease and 15 healthy controls aged 2-18 years were included in the study. Their saliva was analyzed for creatinine, cystatin-C and urea levels using an auto-analyzer and correlated with their existing serum levels. DMFT, gingival index, gingival bleeding and gingival enlargement indices were also assessed. Results: Increased levels of salivary cystatin C, urea (p value <0.001) and creatinine (p value =0.001) were seen in the cases. The deft value was significantly lower (p value <0.001) while the gingival index, gingival bleeding index, and gingival enlargement index were significantly higher in the subjects with renal impairment. Conclusion: Chronic Kidney disease results in many metabolic changes in the body, necessitating frequent biochemical blood analysis. Saliva, being a non-invasive, simple and rapid adjunctive tool, can be used for diagnosing and staging the disease and to check the progression of the condition. Keywords: Chronic Kidney Disease; Renal Dysfunction; Saliva; Cystatin-C; Diagnosis.